Jennifer Chan is not alone - Keller, Tae (Random House, 2022)
Seventh grader Mallory Moss knows the golden rule of middle school: do what you can to fit in. New girl Jennifer Chan, who just moved in across the street, doesn't seem to abide by this rule or any other unspoken rules, especially since she openly talks about believing in aliens. After they start the new year, Jennifer gets bullied by Mallory's friends and Mallory does nothing to stop it. Then Jennifer runs away, and Mallory embarks on a desperate search to find her, combing through Jennifer's journals for clues to her whereabouts and reckoning with her own past mistakes.